Measurement of the Visual Attention Patterns of People with Aphasia: A Preliminary Investigation of Two Types of Human Engagement in Photographic Images. (June 2014) - Thiessen, Amber; Beukelman, David; Ullman, Cara; Longenecker, Maria
Abstract The focus of this investigation was to examine the visual attention patterns of adults with aphasia on task-engaged contextualized images in which a human figure was engaged with the context of the image and camera-engaged contextualized images in which a human figure was looking forward toward the camera. Analysis revealed that adults with aphasia tend to fixate rapidly and frequently on human figures in contextualized images regardless of the type of engagement in the image. In addition, they responded to engagement cues when viewing task-engaged contextualized images by fixating more frequently and more rapidly on the object area of interest for these images than for camera-engaged contextualized images.